The salience of ESG ratings for stock pricing: Evidence from (potentially) confused investors - Aleksandra Rzeźnik; Kathleen Weiss Hanley; Loriana Pelizzon (Leibniz Institute for Financial Research SAFE, 2021)
We exploit a modification to Sustainalytics' environmental, social, and governance (ESG) rating methodology, which is subsequently adopted by Morningstar, to study whether ESG ratings are salient for stock pricing. We show that the inversion of the rating scale but not new information leads some investors to make incorrect assessments about the meaning of the change in ESG ratings. They buy (sell) stocks they misconceive as ESG upgraded (downgraded) even when the opposite is true. This trading behavior exerts transitory price pressure on a↵ected stocks. Our paper highlights the importance of ESG ratings for investors and consequently for asset prices.
Keywords: G11; G12; G23; G59; M14; Q5; 330; Corporate social responsibility; ESG rating agencies; sustainable investments; socially responsible investing; ESG; portfolio choice